the Crime Expressions Of Disbelief in Holly Quran - Marwa Shalash Ta'ma Al-Tamimi / Maithaq Hassan Abdulwahid Al-Salehi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research entitled “ the Crime Expressions Of Disbelief in Holly Quran: A semantic Study” aims at studying the semantic dimensions included in the verbal crime structures of disbelief that are expressed in some Quranic contexts, exploring their functional forms and expressive patterns .     This chapter includes a study of some crime expressions date back in origion to disbelief when are modified their declaration thereof for some semantic and stylistic reasons.